Is it Possible to Democratise Liberalism? Notes about Concepts of Liberty and Equity in Bobbio’s Work (2005)
Starting from the Bobbian thesis according to which it is necessary to democratize liberalism and at the same time liberalize democracy, the text proposes a general approach to the notions of freedom and equality in Norberto Bobbio's work. The article sho